Fundamentalism and the Challemges of Religious Moderation in the New Normal Era - Syarif, Zainuddin; Hannan, Abd (Madania: Jurnal Kajian Keislaman, 2021)
This study examines the phenomenon of religious fundamentalism and its challenges of religious moderation in the midst the implementation of the new normal rules due to the Covid-19 pandemic. There are three focus research problems discussed in this study, namely; fundamentalism, moderation, and the new normal era. By using qualitative research and analysis based on the sociological theory of religion, this study finds a number of findings; first, one of the crucial issues in the midst of the implementation of the new normal Covid-19 policy is to promote the practice of fundamentalism in the name of religion. In many places, the problem of religious fundamentalism in the new normal era occurs in the form of crowd activities and religious crowds which do not follow the health protocol rules; second, the great danger of fundamentalism in the implementation of the new normal, it is not only because of their socio-religious activities which often violate health protocols, but also because their religious paradigm is identical to violence and anarchism, so that it often triggers socio-religious upheaval in society; third, the emergence of the phenomenon of religious fundamentalism in the new normal era today creates its own challenges for the future of moderation of religion throughout the world. The challenge lies in their religious paradigm, which often features fanatical, textual and exclusive attitudes, behaviors and ways of thinking. This attitude clearly contradicts moderation, which has always focused on universality values such as justice (al-adâlah), middle (al-tawassut), balance (al-tawâzun), and tolerance (al-tasâmuh). Studi ini mengkaji fenomena fundamentalisme agama dan problemnya terhadap moderasi beragama di tengah diterapkannya aturan new normal akibat pandemi Covid-19. Terdapat tiga fokus permasalahan penelitian yang dibahas dalam kajian ini, yaitu; fundamentalisme, moderatisme, dan era new normal. Dengan mempergunakan jenis penelitian kualitatif dan analisa berdasarkan teori sosiologi agama, studi ini mendapati sejumlah temuan; pertama, salah satu persoalan krusial di tengah pemberlakuan kebijakan new normal Covid-19 adalah mengemukanya praktik fundamentalisme atas nama agama. Di banyak tempat, problem fundamentalisme agama di era new normal terjadi dalam bentuk aktivitas keramaian dan kerumunan keagamaan yang dalam pelaksananya tidak mengikuti aturan protokol kesehatan; kedua, bahaya besar praktik fundamentalisme di tengah penerapan new normal, itu bukan saja karena aktivitas sosial keagamaan mereka yang seringkali melangar protokol kesehatan, namun juga karena paradigma keagamaan mereka yang identik dengan kekerasan dan anarkisme, sehingga tak jarang memicu gejolak sosial keagamaan di tengah masyarakat; ketiga, munculnya fenomena fundamentalisme agama di era new normal saat ini melahirkan tantangan tersendiri bagi masa depan moderasi agama di seluruh dunia. Tantangan tersebut ada pada paradigma keagamaan mereka yang seringkali menonjolkan sikap, perilaku, dan cara berpikir yang fanatik, tekstual, dan eksklusif. Sikap ini jelas jauh bersebrangan dengan moderatisme yang selama ini senantiasa menitikberatkan pada nilai keadilan universalitas seperti (al- adâlah), tengah-tengah (al-tawassut),  keseimbangan (al-tawâzun), dan toleran (al-tasâmuh).